2010
DOI: 10.1074/jbc.m109.095752
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-mediated Dephosphorylation of Synaptotagmin VI Is Necessary for Acrosomal Exocytosis

Abstract: Regulated secretion is a fundamental process underlying the function of many cell types. In particular, acrosomal exocytosis in mammalian sperm is essential for egg fertilization. In general, exocytosis is initiated by a cytosolic calcium increase. In this report we show that calcium affects several factors during human sperm acrosomal exocytosis. By using an antibody that specifically recognizes synaptotagmin VI phosphorylated at the polybasic region of the C2B domain, we showed that a calciumdependent dephos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Plasma membrane–outer acrosome hybrid vesicles are liberated as a result of the multiple fenestrations that occur in this irreversible reaction, which leads to acrosomal content release of hydrolytic enzymes. Not surprisingly, the fusion machinery conserved in many neuroendocrinal secretory cells and regulated by Ca 2+ is present in sperm and involved in the AR (Bello, Zanetti, Mayorga, & Michaut, 2012; Castillo Bennett, Roggero, Mancifesta, & Mayorga, 2010). At present, where the AR takes place in the female tract and the identity of the molecules inducing this exocytotic reaction is controversial (Jin et al, 2011; Visconti & Florman, 2010; Yanagimachi, 1998).…”
Section: Acrosome Reactionmentioning
confidence: 99%
“…Plasma membrane–outer acrosome hybrid vesicles are liberated as a result of the multiple fenestrations that occur in this irreversible reaction, which leads to acrosomal content release of hydrolytic enzymes. Not surprisingly, the fusion machinery conserved in many neuroendocrinal secretory cells and regulated by Ca 2+ is present in sperm and involved in the AR (Bello, Zanetti, Mayorga, & Michaut, 2012; Castillo Bennett, Roggero, Mancifesta, & Mayorga, 2010). At present, where the AR takes place in the female tract and the identity of the molecules inducing this exocytotic reaction is controversial (Jin et al, 2011; Visconti & Florman, 2010; Yanagimachi, 1998).…”
Section: Acrosome Reactionmentioning
confidence: 99%
“…In the male reproductive system, animal experiments have revealed that CsA and FK506 cause deleterious effects on spermatogenesis and epididymal sperm maturation (3,4). Further, in vitro treatment of spermatozoa with these drugs impairs sperm motility and the acrosome reaction (5,6). These data suggest important roles of calcineurin in male fertility; however, the existence of several isoforms expressed in the testis hampered the clarification of their functions and pharmacological processes.…”
mentioning
confidence: 99%
“…There is virtually no information regarding the involvement of Ser/Thr phosphatases on the effects of P on spermatozoa. There is one report about the effect of PP2B inhibitors on the calcium‐triggered AR (Castillo Bennett et al ., ). Nothing has been reported in relation to calcium influx.…”
Section: Discussionmentioning
confidence: 97%